Neuroinflammation Induced by Intracerebroventricular Injection of Microbial Neuraminidase - Granados-Durán, Pablo; López-Ávalos, María D.; Grondona, Jesús M.; Gómez-Roldán, María del Carmen; Cifuentes, Manuel; Pérez-Martín, Margarita; Alvarez, Martina; Rodríguez de Fonseca, Fernando; Fernández-Llebrez, Pedro (Frontiers in Medicine, 2015)
In the present paper we describe the facts that took place in the rat brain after a single injection of the enzyme neuraminidase from Clostridium perfringens into the right lateral ventricle. After injection, it diffused through the cerebrospinal fluid of the ipsilateral ventricle and the third ventricle, and about 400 µm into the periventricular brain parenchyma. The expression of ICAM1 in the endothelial cells of the periventricular vessels, IBA1 in microglia, and GFAP in astrocytes notably increased in the regions reached by the injected neuraminidase. The subependymal microglia and the ventricular macrophages begun to express IL1β and some appeared to cross the ependymal layer. After about 4 hours of the injection, leukocytes migrated from large venules of the affected choroid plexus, the meninges and the local subependyma, and infiltrated the brain. The invading cells arrived orderly: first neutrophils, then macrophage-monocytes, and last CD8α-positive T-lymphocytes and B-lymphocytes. Leukocytes in the ventricles and the perivascular zones penetrated the brain parenchyma passing through the ependyma and the glia limitans. Thus it is likely that a great part of the damage produced by microorganism invading the brain may be due to their neuraminidase content.